Legal Protection Against Whistleblowers in the Crime of Sexual Harassment (Maqashid al-Shari'ah Perspective) - Fad, Mohammad Farid (Al-'Adl, 2023)
The significance of whistle-blower is the reluctance to take actions that violate public ethics, which can lead to the threat of legal sanctions. The existence of whistleblowers plays a significant role in breaking the chain of sexual harassment. However, the reporting witnesses often lack adequate legal protection and appreciation. This is where the importance of the State's presence in providing legal protection to these witnesses by providing security guarantees. For this reason, it is necessary to study the analysis of legal protection for whistleblowers for criminal acts of sexual harassment in the view of maqashid al-shari'ah, especially in reviewing the concept of maqashid al-shari'ah. This study uses a qualitative approach. Meanwhile, the data collection methods used are literature, documentation, and observation. In analyzing the data, the authors use descriptive analysis with the ushuliyah approach, namely by using the theory of maqashid shari'ah. The results of this study reveal that legal protection for the reporting witness (Whistleblower) of the crime of sexual harassment in the maqashid al-shari'ah perspective is a type of legal protection that mainstreams the common good and rejects harm because the role of the reporting witness is considered urgent in revealing the truth of legal facts. The urgency of legal protection for witnesses reporting sexual harassment is to protect witnesses from attempts at terror and intimidation as part of a joint effort to overcome organized crimes that tend to have a clandestine pattern. When an act of intimidation occurs at the reporter, it causes harm in the form of a threat to the survival and benefit of a person's life. Therefore, within the framework of maqashid al-shari'ah, the Government must enact a law on the protection of whistleblowers of sexual harassment to ensure that law enforcement efforts are guaranteed. The implication is that to realize the principle of maqashid shari'ah, laws, and regulations are needed as part of legal protection efforts for witnesses reporting sexual harassment to close the madharat loopholes arising from the reporting act. The presence of rules that protect whistleblowers from intimidation is evidence of real support for State protection in upholding the rule of law.